Intraductal papillary mucinous neoplasm of the intrahepatic bile duct: a review of literature and a rare case report - Zibari, Lehat; Naseer, Muhammad S.; Patel, Het; Shokouh-Amiri, Hosein; Wellman, Gregory; Dies, David; Browne, Veron; Zibari, Gazi B. (Frontiers in Surgery, 2023)
Background: Intraductal papillary neoplasm of the bile duct (IPNB) is a rare variant of bile duct tumors, which is characterized by papillary or villous growth inside the bile duct. It is extremely rare to have papillary and mucinous features like pancreatic intraductal papillary mucinous neoplasm (IPMN). We are reporting a rare and a case of intraductal papillary mucinous neoplasm of the intrahepatic bile duct. Case Report: A 65-year-old Caucasian male with multiple comorbidities presented to the emergency room with moderate right upper quadrant (RUQ) abdominal constant pain for the last several hours. On physical examination, he was found to have normal vital signs, but his sclera was icteric and had pain to deep palpitation at the RUQ region. His laboratory results were significant for jaundice, elevated liver function tests and creatinine, hyperglycemia, and leukocytosis. Multiple imaging studies revealed a left hepatic lobe heterogeneous mass of 5 cm that demonstrated areas of internal enhancement, mild gall bladder wall edema, dilated gall bladder with mild sludge, and common bile duct (CBD) dilatation of nine mm without evidence of choledocholithiasis. He underwent a CT-guided biopsy of this mass, which revealed Intrahepatic Papillary Mucinous Neoplasm. This case was discussed at the HPB multidisciplinary conference and underwent an uneventful surgery including robotic left partial liver resection, cholecystectomy, and lymphadenectomy. Conclusion: IPMN of the biliary tract may represent a carcinogenesis pathway different from that of CBD carcinoma arising from flat dysplasia. Complete surgical resection should be performed whenever possible because of their significant risk of harboring invasive carcinoma.